The "privatization" of municipal debt - Ivan T. Ivanov; Tom Zimmermann (Federal Reserve Bank of Chicago, 2023)
We study the determinants of local governments' reliance on bank loans using granular data from the Federal Reserve. Governments that are larger, rely on stable revenue sources, or have higher spending relative to revenues are more likely to borrow from banks. About a third of governments in the top revenue quintile have obtained bank loans since 2011, typically accounting for a fifth of their total debt. Declines in revenues, reductions in bond market access, agency rating downgrades, and relationships with financial advisers and underwriters all strongly predict higher bank loan reliance. While resemblance between bank loans and bonds is limited, loans afford governments significant financial flexibility not otherwise available in the municipal bond market. The frequent loan renegotiation and credit line use are both highly responsive to changes in credit quality, thereby tailoring debt contracts to changes in government fundamentals.
Keywords: H74; G21; G32; 330; local government borrowing; debt heterogeneity; fiscal shocks